Does tranexamic acid affect intraventricular hemorrhage growth in acute ICH? An analysis of the STOP-AUST trial. (March 2022) - Yogendrakumar, Vignan; Wu, Teddy Y; Churilov, Leonid; Tatlisumak, Turgut; Strbian, Daniel; Jeng, Jiann-Shing; Kleinig, Timothy J; Sharma, Gagan; Campbell, Bruce CV; Zhao, Henry; Hsu, Chung Y; Meretoja, Atte; et al.
Background: Trials of tranexamic acid (TXA) in acute intracerebral hemorrhage (ICH) have focused on the imaging outcomes of intraparenchymal hematoma growth. However, intraventricular hemorrhage (IVH) growth is also strongly associated with outcome after ICH. Revised definitions of hematoma expansion incorporating IVH growth have been proposed. Aims: We sought to evaluate the effect of TXA on IVH growth. Methods: We analyzed data from the STOP-AUST trial, a prospective randomized trial comparing TXA to placebo in ICH patients presenting ≤ 4.5 h from symptom onset with a CT-angiography spot sign. New IVH development at follow-up, any interval IVH growth, and IVH growth ≥ 1 mL were compared between the treatment groups using logistic regression. The treatment effect of TXA against placebo using conventional (> 6 mL or 33%), and revised definitions of hematoma expansion (> 6 mL or 33% or IVH expansion ≥ 1 mL, > 6 mL or 33%, or any IVH expansion, and > 6 mL or 33% or new IVH development) were also assessed. Treatment effects were adjusted for baseline ICH volume. Results: The analysis population consisted of 99 patients (50 placebo, 49 TXA). New IVH development at follow-up was observed in 6/49 (12%) who received TXA and 13/50 (26%) who received placebo (aOR: 0.38 [95% CI: 0.13–1.13]). Any interval IVH growth was observed in 12/49 (25%) who received TXA versus 26/50 (32%) receiving placebo (aOR: 0.69 [95% CI: 0.28–1.66]). IVH growth ≥ 1 mL did not differ between the two groups. Using revised definitions of hematoma expansion, no significant difference in treatment effect was observed between TXA and placebo. Conclusions: IVH may be attenuated by TXA following ICH; however, studies with larger cohorts are required to investigate this further. Registration: http://www.clinicaltrials.gov ; Unique identifier: NCT01702636.